Nursing of a patient with burning mouth syndrome treated with ear-apex bloodletting combined with auricular acupoint pressing therapy (耳穴放血联合耳穴压丸治疗灼口综合征1例护理体会) - XIAO Hong (肖红); ZHANG Li (张丽); HE Zihao (何子豪); WANG Xing (王星); WANG Dongmei (王冬梅) (中西医结合护理)
This article summarizes the nursing care involved in the treatment of burning mouth syndrome (BMS) through a combination of ear-apex bloodletting and auricular acupoint pressing therapy. Given the pain as the main symptom of disease, a comprehensive nursing assessment on pain and sleep quality was conducted. Based on the Traditional Chinese Medicine syndrome differentiation and routine nursing interventions such as medication guidance, health education and psychological care, the combination of ear-apex bloodletting and auricular acupoint pressing therapy was carried out to relieve the pain and negative emotion and improve the sleep quality of the patient. (本文总结耳穴放血联合耳穴压丸治疗1例灼口综合征(BMS)患者的护理经验。疼痛是BMS患者主要症状, 完善疼痛、睡眠质量评估。基于中医辨证, 在用药指导、健康宣教、心理护理等常规护理基础上, 采用耳穴放血联合耳穴压丸中医适宜技术, 有效改善患者舌痛症状, 缓解负性情绪, 提高睡眠质量。)